Genomic Features and Molecular Function of a Novel Stress-Tolerant Bacillus halotolerans Strain Isolated from an Extreme Environment - Xiaohui Wu; Huijun Wu; Ruoyi Wang; Zhengqi Wang; Yaming Zhang; Qin Gu; Ayaz Farzand; Xue Yang; Mikhail Semenov; Rainer Borriss; Yongli Xie; Xuewen Gao (Biology, 2021)
Due to its topographical position and climatic conditions, the Qinghai–Tibet Plateau possesses abundant microorganism resources. The extremophilic strain KKD1 isolated from Hoh Xil possesses strong stress tolerance, enabling it to propagate under high salinity (13%) and alkalinity (pH 10.0) conditions. In addition, KKD1 exhibits promising biocontrol activity against plant pathogens. To further explore these traits at the genomic level, we performed whole-genome sequencing and analysis. The taxonomic identification according to the average nucleotide identity based on BLAST revealed that KKD1 belongs to Bacillus halotolerans. Genetic screening of KKD1 revealed that its stress resistance mechanism depends on osmotic equilibrium, membrane transportation, and the regulation of ion balance under salt and alkaline stress. The expression of genes involved in these pathways was analyzed using real-time quantitative PCR. The presence of different gene clusters encoding antimicrobial secondary metabolites indicated the various pathways by which KKD1 suppresses phytopathogenic growth. Moreover, the lipopeptides surfactin and fengycin were identified as being significant antifungal components of KKD1. Through comparative genomics analysis, we noticed that KKD1 harbored specific genes involved in stress resistance and biocontrol, thus providing a new perspective on the genomic features of the extremophilic Bacillus species.